Adaptive area-wide management for suppressing spruce budworm outbreaks: effectiveness of the early intervention strategy - Rob C. Johns; S. Edwards; L. Amos-Binks; J. J. Bowden; D. Carleton; C. Edge; C. Hennigar; P. James; D. MacLean; V. Martel; E. R. D. Moise; B. Morin; et al. (Journal of Pest Science, 2026)
In eastern North America, two main insecticide-based strategies are used to manage spruce budworm ( Choristoneura fumiferana ) outbreaks. The traditional ‘Foliage Protection Strategy’ (FPS) focuses on temporarily reducing defoliation and tree mortality in high-value stands, allowing outbreaks to progress naturally in surrounding areas. The ‘Early Intervention Strategy’ (EIS) is an adaptive, area-wide management approach that targets low-density “hotspots” to prevent outbreak growth and spread. We report findings from a 10-year case study (2015–2024) in Atlantic Canada assessing EIS effectiveness. EIS treatments consistently reduced population growth rates, resulting in a 12–67% reduction in hotspot areas compared to untreated areas. Crucially, this suppression curbed the rise and spread of the outbreak across northern New Brunswick, with negligible defoliation observed throughout the study period. By comparison, in a neighboring Quebec study area contemporaneously managed with FPS, the outbreak advanced normally, causing moderate to severe defoliation over ~ 1.7 million hectares by 2024. Moreover, EIS required ~ 80% less insecticide, with 66% of treated areas receiving treatment in only a single year, compared with just 15% under FPS. Our findings provide robust evidence for the effectiveness of EIS when implemented under suitable conditions, highlighting its potential as a proactive outbreak management approach.

Metrics of Urbanicity and Rurality in US-Based Epidemiologic Studies of Ambient Temperature and Health: A Scoping Review - Nicholaus P. Johnson; Alexandra Del Favero-Campbell; Amruta Nori-Sarma; Audrey Amezcua-Smith; Brandon Lewis; Chen Chen; Chengyi Lin; Damien Foo; Garam Byun; Hayon Michelle Choi; Honghyok Kim; Jesse D. Berman; et al. (Current Environmental Health Reports, 2025)

Prenatal PFAS exposures and cardiometabolic health in middle childhood in the MIREC cohort - Alan J. Fossa; Amber M. Hall; George D. Papandonatos; Tye E. Arbuckle; Jillian Ashley-Martin; Michael M. Borghese; Jenny Bruin; Aimin Chen; Mandy Fisher; John E. Krzeczkowski; Bruce P. Lanphear; Amanda J. MacFarlane; et al. (Environmental Research, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

The Cerebellar Cognitive Affective/Schmahmann Syndrome Scale in Spinocerebellar Ataxias - Louisa P. Selvadurai; Susan L. Perlman; Tetsuo Ashizawa; George R. Wilmot; Chiadi U. Onyike; Liana S. Rosenthal; Vikram G. Shakkottai; Henry L. Paulson; Sub H. Subramony; Khalaf O. Bushara; Sheng-Han Kuo; Cameron Dietiker; et al. (The Cerebellum, 2024)

Observing Antarctic Bottom Water in the Southern Ocean - Alessandro Silvano; Sarah Purkey; Arnold L. Gordon; Pasquale Castagno; Andrew L. Stewart; Stephen R. Rintoul; Annie Foppert; Kathryn L. Gunn; Laura Herraiz-Borreguero; Shigeru Aoki; Yoshihiro Nakayama; Alberto C. Naveira Garabato; et al. (Frontiers in Marine Science, 2023)
Dense, cold waters formed on Antarctic continental shelves descend along the Antarctic continental margin, where they mix with other Southern Ocean waters to form Antarctic Bottom Water (AABW). AABW then spreads into the deepest parts of all major ocean basins, isolating heat and carbon from the atmosphere for centuries. Despite AABW’s key role in regulating Earth’s climate on long time scales and in recording Southern Ocean conditions, AABW remains poorly observed. This lack of observational data is mostly due to two factors. First, AABW originates on the Antarctic continental shelf and slope where in situ measurements are limited and ocean observations by satellites are hampered by persistent sea ice cover and long periods of darkness in winter. Second, north of the Antarctic continental slope, AABW is found below approximately 2 km depth, where in situ observations are also scarce and satellites cannot provide direct measurements. Here, we review progress made during the past decades in observing AABW. We describe 1) long-term monitoring obtained by moorings, by ship-based surveys, and beneath ice shelves through bore holes; 2) the recent development of autonomous observing tools in coastal Antarctic and deep ocean systems; and 3) alternative approaches including data assimilation models and satellite-derived proxies. The variety of approaches is beginning to transform our understanding of AABW, including its formation processes, temporal variability, and contribution to the lower limb of the global ocean meridional overturning circulation. In particular, these observations highlight the key role played by winds, sea ice, and the Antarctic Ice Sheet in AABW-related processes. We conclude by discussing future avenues for observing and understanding AABW, impressing the need for a sustained and coordinated observing system.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Integrating very-high-resolution UAS data and airborne imaging spectroscopy to map the fractional composition of Arctic plant functional types in Western Alaska - Dedi Yang; Bailey D. Morrison; Wouter Hanston; Andrew McMahon; Latha Baskaran; Daniel J. Hayes; Charles E. Miller; Shawn P. Serbin (Remote Sensing of Environment, 2023)

The S-Factor, a New Measure of Disease Severity in Spinocerebellar Ataxia: Findings and Implications - Louisa P. Selvadurai; Susan L. Perlman; George R. Wilmot; Sub H. Subramony; Christopher M. Gomez; Tetsuo Ashizawa; Henry L. Paulson; Chiadi U. Onyike; Liana S. Rosenthal; Haris I. Sair; Sheng-Han Kuo; Eva-Maria Ratai; et al. (The Cerebellum, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Conventional versus drug-eluting embolic transarterial chemoembolization with doxorubicin: comparative drug delivery, pharmacokinetics, and treatment response in a rabbit VX2 tumor model - Ron C. Gaba; Ramzy C. Khabbaz; Ruth N. Muchiri; Joseph D. Morrison; Lobna Elkhadragy; William M. Totura; Jonathan P. Samuelson; Herbert E. Whiteley; Ryan L. Deaton; Peter L. Nguyen; Maria Sverdlov; Jeremy J. Johnson; et al. (Drug Delivery and Translational Research, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Human Actions Alter Tidal Marsh Seascapes and the Provision of Ecosystem Services - Ben L. Gilby; Michael P. Weinstein; Ronald Baker; Just Cebrian; Scott B. Alford; Ariella Chelsky; Denise Colombano; Rod M. Connolly; Carolyn A. Currin; Ilka C. Feller; Alyssa Frank; Janelle A. Goeke; et al. (Estuaries and Coasts, 2021)

Source Switching Maintains Dissolved Organic Matter Chemostasis Across Discharge Levels in a Large Temperate River Network - J. D. Hosen; K. S. Aho; J. H. Fair; E. D. Kyzivat; S. Matt; J. Morrison; A. Stubbins; L. C. Weber; B. Yoon; P. A. Raymond (Ecosystems, 2021)

Biological Control of the Noxious Weed Angled Onion (Allium triquetrum) Thwarted by Endophytic Bacteria in Victoria, Australia - P. Tehranchian; R. J. Adair; T. T. H. Van; P. D. Morrison; H. Williams; A. C. Lawrie (Australasian Plant Pathology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Enhancement of primary production during drought in a temperate watershed is greater in larger rivers than headwater streams - J. D. Hosen; K. S. Aho; A. P. Appling; E. C. Creech; J. H. Fair; R. O. Hall; E. D. Kyzivat; R. S. Lowenthal; S. Matt; J. Morrison; J. E. Saiers; J. B. Shanley; et al. (Limnology and Oceanography, 2019)
Drought is common in rivers, yet how this disturbance regulates metabolic activity across network scales is largely unknown. Drought often lowers gross primary production (GPP) and ecosystem respiration (ER) in small headwaters but by contrast can enhance GPP and cause algal blooms in downstream estuaries. We estimated ecosystem metabolism across a nested network of 13 reaches from headwaters to the main stem of the Connecticut River from 2015 through 2017, which encompassed a pronounced drought. During drought, GPP and ER increased, but with greater enhancement in larger rivers. Responses of GPP and ER were partially due to warmer temperatures associated with drought, particularly in the larger rivers where temperatures during summer drought were > 10°C higher than typical summer baseflow. The larger rivers also had low canopy cover, which allowed primary producers to take advantage of lower turbidity and fewer cloudy days during drought. We conclude that GPP is enhanced by higher temperature, lower turbidity, and longer water residence times that are all a function of low discharge, but ecosystem response in temperate watersheds to these drivers depends on light availability regulated by riparian canopy cover. In larger rivers, GPP increased more than ER during drought, even leading to temporary autotrophy, an otherwise rare event in the typically light‐limited heterotrophic Connecticut River main stem. With climate change, rivers and streams may become warmer and drought frequency and severity may increase. Such changes may increase autotrophy in rivers with broad implications for carbon cycling and water quality in aquatic ecosystems.

Leveraging linkage evidence to identify low-frequency and rare variants on 16p13 associated with blood pressure using TOPMed whole genome sequencing data - Karen Y. He; Xiaoyin Li; Tanika N. Kelly; Jingjing Liang; Brian E. Cade; Themistocles L. Assimes; Lewis C. Becker; Amber L. Beitelshees; Adam P. Bress; Yen-Pei Christy Chang; Yii-Der Ida Chen; Paul S. de Vries; et al. (Human Genetics, 2019)

Medical Knowledge Assessment by Hematology and Medical Oncology In-Training Examinations Are Better Than Program Director Assessments at Predicting Subspecialty Certification Examination Performance - Frances A. Collichio; Brian J. Hess; Elaine A. Muchmore; Lauren Duhigg; Rebecca S. Lipner; Steven Haist; Janine L. Hawley; Carol A. Morrison; Charles P. Clayton; Marilyn J. Raymond; Karen M. Kayoumi; Scott D. Gitlin (Journal of Cancer Education, 2017)

Transcriptomic effects of adenosine 2A receptor deletion in healthy and endotoxemic murine myocardium - Kevin J. Ashton; Melissa E. Reichelt; S. Jamal Mustafa; Bunyen Teng; Catherine Ledent; Lea M. D. Delbridge; Polly A. Hofmann; R. Ray Morrison; John P. Headrick (Purinergic Signalling, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Differences in carbon source utilisation by orchid mycorrhizal fungi from common and endangered species of Caladenia (Orchidaceae) - S. Mehra; P. D. Morrison; F. Coates; A. C. Lawrie (Mycorrhiza, 2017)

Multi-generational evaluation of genetic diversity and parentage in captive southern pygmy perch (Nannoperca australis) - Catherine R. M. Attard; Chris J. Brauer; Jacob D. Van Zoelen; Minami Sasaki; Michael P. Hammer; Leslie Morrison; James O. Harris; Luciana M. Möller; Luciano B. Beheregaray (Conservation Genetics, 2016)

Distribution mapping of world grassland types - A. P. Dixon; D. Faber‐Langendoen; C. Josse; J. Morrison; C. J. Loucks (Journal of Biogeography, 2014)
Aim National and international policy frameworks, such as the European Union's Renewable Energy Directive, increasingly seek to conserve and reference ‘highly biodiverse grasslands’. However, to date there is no systematic global characterization and distribution map for grassland types. To address this gap, we first propose a systematic definition of grassland. We then integrate International Vegetation Classification (IVC) grassland types with the map of Terrestrial Ecoregions of the World (TEOW). Location Global. Methods We developed a broad definition of grassland as a distinct biotic and ecological unit, noting its similarity to savanna and distinguishing it from woodland and wetland. A grassland is defined as a non‐wetland type with at least 10% vegetation cover, dominated or co‐dominated by graminoid and forb growth forms, and where the trees form a single‐layer canopy with either less than 10% cover and 5 m height (temperate) or less than 40% cover and 8 m height (tropical). We used the IVC division level to classify grasslands into major regional types. We developed an ecologically meaningful spatial catalogue of IVC grassland types by listing IVC grassland formations and divisions where grassland currently occupies, or historically occupied, at least 10% of an ecoregion in the TEOW framework. Results We created a global biogeographical characterization of the Earth's grassland types, describing approximately 75% of IVC grassland divisions with ecoregions. We mapped 49 IVC grassland divisions. Sixteen additional IVC grassland divisions are absent from the map because of the fine‐scale distribution of these grassland types. Main conclusions The framework provided by our geographical mapping effort provides a systematic overview of grasslands and sets the stage for more detailed classification and mapping at finer scales. Each regional grassland type can be characterized in terms of its range of biodiversity, thereby assisting in future policy initiatives.

Winter weather versus group thermoregulation: what determines survival in hibernating mammals? - V. P. Patil; S. F. Morrison; T. J. Karels; D. S. Hik (Oecologia, 2013)

Use of A tlantic salmon, S almo salar L., farm treatment data and bioassays to assess for resistance of sea lice, L epeophtheirus salmonis , to emamectin benzoate ( SLICE ® ) in B ritish C olumbia, C anada - S M Saksida; D Morrison; P McKenzie; B Milligan; E Downey; B Boyce; A Eaves (Journal of Fish Diseases, 2013)

Nitrogen enrichment modifies plant community structure via changes to plant–soil feedback - P. Manning; S. A. Morrison; M. Bonkowski; R. D. Bardgett (Oecologia, 2008)

Detection of meticillin-resistant Staphylococcus aureus and Panton-Valentine leukocidin directly from clinical samples and the development of a multiplex assay using real-time polymerase chain reaction - L. Renwick; A. Hardie; E. K. Girvan; M. Smith; G. Leadbetter; E. Claas; D. Morrison; A. P. Gibb; J. Dave; K. E. Templeton (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Spatial‐temporal variability in diazotroph assemblages in Chesapeake Bay using an oligonucleotide nifH microarray - Pia H. Moisander; Amanda E. Morrison; Bess B. Ward; Bethany D. Jenkins; Jonathan P. Zehr (Environmental Microbiology, 2007)
Summary The distribution of nitrogen‐fixing microorganisms in the Chesapeake Bay was investigated using fingerprints from a nifH microarray comprised of 706 60‐mer oligonucleotide nifH probes representing cultivated organisms and environmental clones from different nifH clusters. Diverse nifH targets, amplified from samples using degenerate nifH primers, were detected in water column and sediment samples collected in April and October, 2001–2002. Total nifH richness and diversity (Simpson's and Shannon indices) were highest at the most riverine, oligohaline North Bay station. In most samples, the highest diversity was in nifH Cluster 3, which includes many anaerobes, while Cluster 1 (α‐, β‐ γ‐ Proteobacteria, Cyanobacteria) targets had the greatest microarray signal intensities. In a multidimensional scaling analysis, deep water communities from April and October were similar within each of the sampling sites, while the surface communities had more variability. Diazotroph communities in the water column in the North Bay were distinct from the Mid‐ and South Bay communities, and there was a gradual change in sediment diazotroph assemblages from the North to the South Bay. Diazotrophic assemblages from the majority of the water column samples from the Mid‐ and South Bay clustered with the sediment assemblage in Mid‐Bay. Dissolved inorganic nitrogen, salinity, dissolved organic carbon and dissolved organic phosphorus had a significant relationship with the diazotrophic bacterioplankton community. Higher diversity in the freshwater end of the system may reflect variability in disturbance rates and environmental conditions such as forms and concentrations of organic matter, nutrients and oxygen.

Multicenter retrospective development and validation of a clinical prediction rule for nosocomial invasive candidiasis in the intensive care setting - L. Ostrosky-Zeichner; C. Sable; J. Sobel; B. D. Alexander; G. Donowitz; V. Kan; C. A. Kauffman; D. Kett; R. A. Larsen; V. Morrison; M. Nucci; P. G. Pappas; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

The effects of age and streptozotocin diabetes on the sympathetic innervation in the rat penis - J. F. B. Morrison; D. J. Pallot; R. Sheen; S. Dhanasekaran; E. P. K. Mensah-Brown (Molecular and Cellular Biochemistry, 2007)

A genetic test for recruitment enhancement in Chesapeake Bay oysters, Crassostrea virginica, after population supplementation with a disease tolerant strain - Matthew P. Hare; Standish K. Allen; Paulette Bloomer; Mark D. Camara; Ryan B. Carnegie; Jenna Murfree; Mark Luckenbach; Donald Meritt; Cheryl Morrison; Kennedy Paynter; Kimberly S. Reece; Colin G. Rose (Conservation Genetics, 2006)

Nest- and colony-mate recognition in polydomous colonies of meat ants (Iridomyrmex purpureus) - E. van Wilgenburg; D. Ryan; P. Morrison; P. J. Marriott; M. A. Elgar (The Science of Nature, 2006)